ZrO2 and ZrO2-Y2O3 Phase Structure in Films and Powders - Caruso, R. (1994)
Zirconia and zirconia-yttria coating films and powders obtained by the sol-gel route using a zirconium alkoxide as starting material and acid and neutral catalytic were investigated by the Perturbed Angular Correlations method (PAC), XRD, DTA and TGA. The hyperfine interaction was measured either during heat treatements or after annealing the samples at increasing temperatures up to 1200°C. All samples have presented a high fraction of crystalline phases at low temperatures. The yttria doped cubic zirconia has not shown the phase transition to the monoclinic phase. Pure zirconia powders produced in neutral hydrolysis and zirconia coatings produced in acid catalysis stabilized the tetragonal phase in a high fraction and up to high temperatures.